Professional self-determination theory of senior pupils in Russian psychology - E. P. Shutova; A. S. Velikanova (Gerasimova) (Вестник университета)
The article analyses the psychological literature on the problem of senior pupils’ professional self-determination. The author’s theoretical and methodological position is elaborated and the results of its approbation are presented. It is shown that the available approaches can be divided into two main groups. Some researchers focus on the goal and end result of vocational self-determination, while others seek to reveal the algorithm of the process itself and/or its stages. Researchers are unanimous in their opinion that the choice of an occupation by senior pupils is the first and most responsible stage of professional self-determination for the individual as a whole. At the same time, the senior pupils’ professional self-determination concepts, which would reflect the unity of theoretical positions and methods of its study, are practically not presented in national psychology. To overcome the existing limitations, the article proposes to consider the senior pupils’ professional self-determination from the position of the activity approach as a special kind of activity with its own structure. The motivational component is the motives for choosing a career, while the operational component is the senior pupils’ professional identity status. The empirical study results of the of formation level of senior pupils’ professional self-determination are discussed on the basis of the activity methodology.